HUBUNGAN KONTROL GLIKEMIK PENGIDAP DIABETES MELITUS TIPE 2 DENGAN KEJADIAN NEUROPATI DIABETIK DI RSUD DR. PIRNGADI KOTA MEDAN - LAURA OCTAVINA SIAGIAN (JURNAL ILMIAH MAKSITEK, 2023)
Type 2 diabetes mellitus is a metabolic disorder characterized by an elevation in blood glucose levels, leading to a reduction in insulin production by pancreatic beta cells or the body’s response to insulin (insulin resistance). Blood glucose (glycemic) regulation is a highly effective therapeutic measure in reducing the incidence or impeding the progression of neuropathy. The utilization of HbA1c measurement constitutes an efficient glycemic monitoring method to obtain an overview of the average blood glucose levels over a period of two or three preceding months.The aim of this study is to determine the influence of glycemic control on individuals with type 2 diabetes mellitus towards the occurrence of neuropathy at RSUD Dr. Pirngadi Kota Medan.The research methodology employed in this study is observational analytics utilizing a cross-sectional approach.The research findings revealed a significant influence between glycemic control (HbA1c, fasting blood glucose, and 2-hour postprandial blood glucose) among individuals with the type 2 diabetes mellitus and the occurrence of diabetic neuropathy. Among these glycemic control factors, HbA1c exhibited a more dominant impact on the occurrence of diabetic neuropathy.